2004
DOI: 10.1016/j.pep.2004.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Function of the signal peptide and N- and C-terminal propeptides in the leucine aminopeptidase from Aeromonas proteolytica

Abstract: The leucine aminopeptidase from Aeromonas proteolytica (also known as Vibrio proteolyticus) (AAP) is a metalloenzyme with broad substrate specificity. The open reading frame (ORF) for AAP encodes a 54 kDa enzyme, however, the extracellular enzyme has a molecular weight of 43 kDa. This form of AAP is further processed to a mature, thermostable 32 kDa form but the exact nature of this process is unknown. Over-expression of different forms of AAP in Escherichia coli (with AAP's native leader sequence, with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…AAP is expressed with sequences that need to be proteolytically removed for full activity and crystallization. The protein was processed as previously reported (30). The mostly nonspecific endopeptidase, proteinase K, was added to the AAP solution to give a final concentration of 20 nM proteinase K, and the sample was incubated at 37 °C with mild rocking.…”
Section: Protein Purificationmentioning
confidence: 99%
“…AAP is expressed with sequences that need to be proteolytically removed for full activity and crystallization. The protein was processed as previously reported (30). The mostly nonspecific endopeptidase, proteinase K, was added to the AAP solution to give a final concentration of 20 nM proteinase K, and the sample was incubated at 37 °C with mild rocking.…”
Section: Protein Purificationmentioning
confidence: 99%
“…The 54 kDa VpAP* polypeptide consists of a 21 amino acid signal peptide, an 85 amino acid N-terminal propeptide, a 299 amino acid mature region, and a 99 amino acid C-terminal propeptide (Figure 1). The signal peptide is required for secretion, the N-terminal propeptide is required for folding but its presence inhibits catalytic activity, and the C-terminal propeptide is of undetermined function but appears to be species-specific [71, 72]. VpAP* is processed to the final 32 kDa mature protein only after secretion and during purification; roles in the processing of VpAP* have been proposed for VpAP* itself (and VpAP) in autoprocessing, for a co-expressed neutral protease, and for a heat-treatment step that has been traditionally employed [73-75].…”
Section: Introductory Statementmentioning
confidence: 99%
“…A highly detailed investigation into the requirements for the isolation of VpAP heterologously expressed in E. coli has been described by Bzymek, Holz and coworkers [71], and the resulting protocol has yielded both recombinant wild-type and site-directed variant forms of VpAP for subsequent crystallographic and physicochemical studies [38, 61-63, 71]. As suggested by earlier work [72, 77-79], it was found that VpAP was best expressed as a 52 kDa proenzyme (ΔspVpAP*; lacking the first 23 amino acids); the use of an appropriate leader sequence ( e.g.…”
Section: Introductory Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained data indicate the propeptide-assisted folding mechanism of the Mpr folding. In many proteases including thermolysin-like ones [1,3,22,[28][29][30], the N-terminal propeptide acts as an intramolecular chaperone in propeptide-assisted folding. However, our data provides the first demonstration that Mpr variants generated in cis and in trans differ in the ability to hydrolyze peptide substrates.…”
Section: Discussionmentioning
confidence: 99%